Impact on blood loss and transfusion rates following administration of tranexamic acid in major oncological abdominal and pelvic surgery: A systematic review and meta‐analysis. Issue 3 (26th April 2022) - Fowler, Hayley; Law, Jennifer; Tham, Su Ming; Gunaravi, Sisyena A.; Houghton, Neil; Clifford, Rachael E.; Fok, Matthew; Barker, Jonathan A.; Vimalachandran, Dale
Abstract: Background and Objectives: Major bleeding and receiving blood products in cancer surgery are associated with increased postoperative complications and worse outcomes. Tranexamic acid (TXA) reduces blood loss and improves outcomes in various surgical specialities. We performed a systematic review and meta‐analysis to investigate TXA use on blood loss in elective abdominal and pelvic cancer surgery. Methods: A literature search was performed for studies comparing intravenous TXA versus placebo/no TXA in patients undergoing major elective abdominal or pelvic cancer surgery. Results: Twelve articles met the inclusion criteria, consisting of 723 patients who received TXA and 659 controls. Patients receiving TXA were less likely to receive a red blood cell (RBC) transfusion ( p  < 0.001, OR 0.4 95% CI [0.25, 0.63]) and experienced less blood loss ( p  < 0.001, MD −197.8 ml, 95% CI [−275.69, −119.84]). The TXA group experienced a smaller reduction in haemoglobin ( p  = 0.001, MD –0.45 mmol/L, 95% CI [−0.73, −0.18]). There was no difference in venous thromboembolism (VTE) rates ( p  = 0.95, OR 0.98, 95% CI [0.46, 2.08]). Conclusions: TXA use reduced blood loss and RBC transfusion requirements perioperatively, with no significant increased risk of VTE. However, further studies are required to assess its benefit for cancer surgery in some sub‐specialities.